Synthesis of Benzimidazolyl-6-amino-?-D-glucopyranoses - Umare, V.D.; Ingle, V.N.; Wanare, R.K (Asian Journal of Chemistry, 2010)
Benzimidazolyl-6-amino-β-D-glucopyranoses (5a-j) has been rapidly, selectively and efficiently synthesized by condensation of 2-substituted-6-amino-1H-benzimidazoles with acetobromoglucose. The structures were assigned with elemental analysis, melting point and spectral analysis.